A nano core-shell cobalt-based catalyst and its preparation and application
By designing a nano-core-shell cobalt-based catalyst and utilizing the nano-core-shell structure of metallic cobalt and cobalt carbide, we solve the problem of product selectivity control when directly producing mixed alcohols and olefins from synthesis gas, achieving high selectivity and high yield of high-carbon Alcohol and Alkene Preparation.
Patent Information
- Application Number
- CN202111182311.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-11
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-10-11
AI Technical Summary
The prior art has not yet effectively solved the problem of product selectivity regulation when syngas is directly used to produce mixed alcohols and olefins, especially high-value-added high-carbon alcohols and high-carbon olefin contents.
A nano-core-shell cobalt-based catalyst is designed. The catalyst is composed of a porous carbon carrier, additives and cobalt nanoparticles supported on the porous carbon carrier. By constructing a nano-core-shell structure composed of metallic cobalt and cobalt carbide, a dual function is formed. Catalyst, improves the selectivity of higher carbon alcohols and olefins.
Achieve high-selectivity conversion of synthesis gas into mixed alcohols and olefins. The content of high-carbon alcohols and high-carbon olefins exceeds 80% of the total alcohols and olefins. The catalyst has excellent catalytic performance, extremely low methane selectivity, total selectivity and yield. high.
Smart Images

Figure CN115957786B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst, in particular to a preparation method and application of a nano core-shell cobalt-based catalyst for directly preparing mixed alcohol and olefins from synthesis gas. Background Art
[0002] The high value-added conversion and utilization of coal resources is an important research topic in my country's energy field. At present, the technology of directly synthesizing clean oil products (Fischer-Tropsch synthesis) from coal via synthesis gas (mixed gas of CO and H2) has matured at home and abroad. Enterprises such as Sasol, Shell, Shenhua Ningmei, Yitai, Lu'an, and Yankuang have achieved industrial production of Fischer-Tropsch synthesis oil products at the million-ton level. In particular, the promotion and application of the iron-based slurry bed Fischer-Tropsch synthesis technology developed by my country Science and Technology Synthetic Oil Company has made my country's coal-to-oil technology a world leader. At the same time, the technology of preparing chemicals such as alcohols and olefins from coal via synthesis gas in one step is attracting widespread attention from the scientific and industrial communities due to its advantages of high product added value and good economic benefits, and has broad application prospects. However, compared with Fischer-Tropsch synthesis oil, this technology is not yet mature, mainly because there are many challenging scientific problems that have not been effectively solved, and the control effect of product selectivity needs to be improved. The main reason is that the synthesis of alcohol requires the synergistic effect of two active centers, and the interface of the two active centers is the active site of the synthesis of alcohol. Olefins require active sites with special morphology to be generated with high selectivity. Therefore, designing new catalysts and constructing a catalyst system with a fine structure of dual active centers is the key to obtaining catalysts with high yields of synthetic alcohols and olefins.
[0003] At present, the main catalysts for preparing mixed alcohols from syngas are divided into four categories, namely modified methanol catalysts, modified Fischer-Tropsch catalysts, Rh-based catalysts and Mo-based catalysts. Rh-based catalysts are expensive and have low industrial application value, so only laboratory basic research is involved. The content of low-carbon alcohols in the products of Mo-based catalysts is high, so there are fewer related studies. Among them, there are more studies on modified methanol catalysts and modified Fischer-Tropsch catalysts. Modified methanol catalysts are mainly Cu-based catalysts, with Cu as the main active component. By doping a series of other metals, the selectivity of high-carbon alcohols in the product is improved, but methanol is still the main component. The modified Fischer-Tropsch catalyst is based on the cobalt-based catalyst of Fischer-Tropsch synthesis. By adding a second active component, the insertion ability of CO is enhanced, thereby improving the selectivity of alcohols. The main research focuses on Cu-Co catalysts, that is, a catalyst system containing two active centers of metal Cu and metal Co. Metal Co dissociates CO and forms a hydrocarbon chain, and metal Cu plays a role in non-dissociative adsorption of CO and inserts the hydrocarbon chain to generate alcohol. For example, the CoCuMn catalyst reported by Xiang et al. can achieve high-selectivity synthesis of mixed alcohols. However, the content of methanol and low-carbon alcohol (C2-C5 alcohol) in this type of catalyst is relatively high, and the high-value-added high-carbon alcohol (C 6+Alcohol) content is low. Our research group proposed a Co-Co2C catalyst, which is characterized by forming a dual active center with in-situ generated Co2C and metal Co, and using the property of Co2C to non-dissociatively adsorb CO to generate alcohol at the interface of Co and Co2C. A series of methods for synthesizing such catalysts were further reported (Chinese patents 20120077138.2, 201210225885, 20140581924, etc.). It mainly selects carbon materials as carriers, adopts a series of auxiliary agent modulation methods, increases the content of in-situ generated Co2C during the reaction, constructs active sites with both metal Co and Co2C, and realizes high selectivity of synthesis gas to produce mixed alcohols. The selectivity of mixed alcohols can reach more than 40%, which has potential industrial application significance. However, the above work did not clearly explain the structural characteristics of the active sites of the catalyst, nor did it propose the preparation method required to construct active sites with special structures.
[0004] However, we found that in addition to mixed alcohols, syngas can be converted into olefins on the catalyst, and olefins can generate corresponding alcohols through simple hydroformylation reactions. Therefore, improving the overall selectivity of olefins and mixed alcohols is actually helpful to improve the overall alcohol selectivity, and the purpose of preparing mixed alcohols with high selectivity from syngas can be achieved. As a special substance, Co2C can catalyze the conversion of syngas into olefins with high selectivity, such as the high selectivity of rhombic cobalt carbide to prepare low-carbon olefins reported by Zhong et al. (Nature, 2016). However, the activity of Co2C is closely related to its structure. For example, bulk Co2C does not have Fischer-Tropsch activity and is not an intermediate (JACS, 1946). Therefore, the design of the catalyst microstructure, especially the regulation of the existence state of Co2C and its matching mode with the metal Co phase, is the key to obtaining high overall selectivity of alcohols and olefins. There are also a large number of articles reporting the work of improving alcohol selectivity by designing Co2C nanoparticles, but none of them have achieved significant breakthroughs, mainly limited by low selectivity, activity and yield, and there are no corresponding industrial application reports.
[0005] There are many structures of catalyst active sites, among which the core-shell structure is a typical catalyst active site structure, and there are also reports on the application of such catalysts in syngas to oil. For example, Chinese patent 201711449809.2 reported a cobalt-based catalyst with a nano-core-shell structure that can synthesize C 10 -C 20A liquid fuel with concentrated fractions, whose core-shell structure is composed of transition metals and cobalt. Chinese Patent 201510299062 discloses a core-shell type catalyst for preparing low-carbon olefins from syngas, with cobalt and a carrier as the core and silica zeolite as the shell. Chinese Patent 201010139054.8 discloses a method for preparing a core-shell cobalt-based catalyst for preparing middle distillate oil from syngas and its application, wherein cobalt trioxide nanoparticles are wrapped by a silica shell to form a core-shell structure with high middle distillate oil selectivity. However, none of the above catalysts involve the high selectivity of syngas to prepare mixed alcohols and high-carbon olefins, and their design concepts are also different from the dual active center interaction mechanism described in the present invention.
[0006] Therefore, by designing the microscopic fine structure of the catalyst active site, inventing a catalyst that can highly selectively convert synthesis gas to mixed alcohols and olefins, especially to increase the content of high-value-added high-carbon alcohols and high-carbon olefins, has important academic and industrial significance. Summary of the invention
[0007] The invention provides a nano core-shell cobalt-based catalyst, which comprises a porous carbon carrier, an auxiliary agent and cobalt nanoparticles with a core-shell structure and loaded on the porous carbon carrier.
[0008] A nano core-shell cobalt-based catalyst, wherein the cobalt content in the catalyst is between 10wt% and 30wt%, preferably 15wt%-25wt%, and more preferably 15wt%-20wt%; the additives include transition metal additives and alkali metal and / or alkaline earth metal additives; the transition metal additive is one or more of Mn, La and Ce, and the weight content thereof in the catalyst is between 0.1wt% and 5wt%, preferably 0.3wt%-3wt%, and more preferably 0.5wt%-2wt% based on the mass of the metal; the alkali metal or alkaline earth metal additive is one or more of Li, Na, K, Ca, Mg and Ba, and the weight content thereof in the catalyst is between 0.01wt% and 2wt%, and preferably 0.1wt%-1wt%.
[0009] A nano core-shell cobalt-based catalyst, wherein the particle size of core-shell structured cobalt nanoparticles is 10-15nm, the particle size of metal cobalt crystal particles as cores is 2-6nm, and the metal cobalt is coated with a cobalt carbide shell to form a core-shell structure, wherein the cobalt carbide is a compound Co2C formed by cobalt and carbon.
[0010] A method for preparing a nano core-shell cobalt-based catalyst comprises the following steps:
[0011] 1) treating activated carbon with a mixture of water vapor and nitrogen at high temperature to obtain a carbon carrier; the volume concentration of water vapor in nitrogen is 10-50%, preferably 20-30%, the treatment temperature is 600-900° C., preferably 700-800° C., and the treatment time is 1-5 hours, preferably 2-4 hours;
[0012] 2) dissolving a soluble cobalt salt in water to prepare an impregnation solution, and using an impregnation method (preferably an equal volume impregnation method) to load the cobalt precursor on a carbon support to prepare a catalyst precursor;
[0013] 3) The catalyst precursor is calcined in an inert gas to convert the cobalt precursor into cobalt oxide nanoparticles dispersed on the surface of the carrier to obtain a solid sample;
[0014] 4) adding the precursor salt of the transition metal additive into deionized water to prepare a solution, then adding the solid sample obtained in (3), stirring, adding one or both of sodium carbonate and potassium carbonate, adjusting the pH value to 9-12, stirring, filtering, washing to neutrality and drying;
[0015] 5) The solid obtained in (4) is impregnated with an aqueous solution of an alkali metal and / or alkaline earth metal salt by an impregnation method (preferably an equal volume impregnation method), and then dried and calcined again in an inert gas; this step is mainly to introduce a sufficient amount of alkali metal into the catalyst. At the same time, the amount of alkali metal in the catalyst can be accurately controlled.
[0016] 6) reducing the catalyst precursor obtained in step (5) to convert the cobalt oxide into metallic cobalt nanoparticles to obtain a reduced catalyst;
[0017] 7) treating the reduced catalyst obtained in (6) under a carbon monoxide atmosphere, during which the metal cobalt nanoparticles are reconstructed to form the nano core-shell cobalt-based catalyst; the treatment temperature is between 400 and 500° C., preferably 450 to 490° C.; the treatment time is between 2 and 10 hours, preferably 3 to 7 hours.
[0018] The activated carbon described in step (1) has a specific surface area of 800 to 1000 m 2 / g, and the pore volume is between 0.8 and 1.2cc / g.
[0019] The transition metal auxiliary salts described in step (4) include one or more chlorides, sulfates and nitrates of one or more of Mn, La and Ce; the alkali metal and alkaline earth metal salts described in step (5) include one or more chlorides, sulfates and nitrates of one or more of Li, Na, K, Ca, Mg and Ba.
[0020] The calcination temperature in steps (3) and (5) is between 220 and 400° C., preferably 300 to 350° C., and the calcination atmosphere is one or both of nitrogen and argon. The calcination time is between 2 and 6 hours, preferably 3 to 4 hours.
[0021] The reducing atmosphere in step (6) is hydrogen or a mixture of hydrogen and nitrogen, the volume content of hydrogen in the reducing atmosphere is between 50% and 100%, preferably 70% to 100%; the reducing temperature is between 300 and 500° C., preferably 400 to 470° C. The reducing time is between 2 and 6 hours, preferably 3 to 4 hours.
[0022] The nano core-shell cobalt-based catalyst is used for direct preparation of mixed alcohols and olefins from synthesis gas. In a slurry bed reactor or a fixed bed reactor, the molar ratio of CO to H2 is 1:1-1:3, the reaction temperature is 190-270°C, and the reaction pressure is 2.5-6MPa. The total selectivity of mixed alcohols and olefins is higher than 70wt%. Under typical operating conditions (3MPa, 210°C), the space-time yield of mixed alcohols and olefins is higher than 0.5g / gcat·h.
[0023] The porosity, specific surface area, cobalt and additive content of the synthesis gas catalytic conversion catalyst prepared by the present invention are characterized by BET and ICP methods, and the nano core-shell structure is characterized by spherical aberration corrected transmission electron microscopy (ac-STEM).
[0024] Compared with the prior art, the beneficial effects of the nano core-shell cobalt-based catalyst for directly preparing mixed alcohols and olefins from synthesis gas provided by the present invention are mainly reflected in the following aspects:
[0025] (1) The catalyst provided by the present invention has excellent catalytic performance, extremely low methane selectivity (<8%), and the product distribution shows the characteristics of high total selectivity and high yield of mixed alcohols and olefins, wherein the total alcohol selectivity generally exceeds 40%, and the olefin selectivity generally exceeds 30%. Under typical operating conditions, the total space-time yield of the two exceeds 0.5 g / gcat·h, and the high carbon alcohol (C 6+ Alcohols) and higher olefins (C 5+ The content of olefins in the total alcohols and olefins exceeds 80%.
[0026] (2) The catalyst constructs a nano-core-shell structure composed of metal cobalt and cobalt carbide to form a bifunctional catalyst. The active metal cobalt promotes the hydrogenation of CO to form hydrocarbon chains and the cobalt carbide promotes the insertion of CO into hydrocarbon chains to form alcohols, thereby improving the selectivity of high-carbon alcohols. The "carbon-rich and hydrogen-deficient" characteristics of the interface between metal cobalt and unsaturated cobalt carbide promote the dissociation of hydrocarbon chains and improve the selectivity of olefins.
[0027] (3) The excellent chemical inertness and thermal stability of the carbon support, as well as its well-developed pore structure, play a good confinement role, regulate the product selectivity, and are conducive to the formation of intermediate distillate products.
[0028] (4) The catalyst preparation process is simple and controllable, and can be easily scaled up.
[0029] In summary, the nano core-shell cobalt-based catalyst provided by the present invention is used for direct preparation of mixed alcohols and olefins from synthesis gas, which can not only obtain high selectivity and yield of alcohols and olefins, but also has concentrated product distribution, simple catalyst preparation method, low cost and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is an ac-STEM image of the active site structure of the nano core-shell cobalt-based catalyst before synthesis gas treatment for directly preparing mixed alcohols and olefins from synthesis gas after the catalyst provided by the present invention is reduced.
[0031] Figure 2 This is an ac-STEM image of the nano core-shell cobalt-based catalyst provided by the present invention.
[0032] Figure 3 This is the ac-STEM image of the conventional carbon-supported cobalt-based catalyst 15Co / C in the comparative example of the present invention.
[0033] Figure 4 This is an ac-STEM image of the active site structure of the Co-0.5Al-0.1Na / C catalyst in comparative example 15 of the present invention.
[0034] Figure 5 This is an ac-STEM image of the active site structure of the 15Co-0.5Mn / C catalyst of the comparative example of the present invention.
[0035] Figure 6 This is an ac-STEM image of the active site structure after the reaction of the comparative example 15Co-0.5Mn-0.1Na / C catalyst of the present invention without CO treatment. DETAILED DESCRIPTION
[0036] The characterization and preparation method of the nano core-shell cobalt-based catalyst provided by the present invention are further described in detail below.
[0037] The specific surface area and pore size distribution of activated carbon and carbon carrier were determined on the AS-1 adsorption instrument of QUANTACHROME. The samples were first degassed at 573K for 3h and then nitrogen adsorption was tested at liquid nitrogen temperature. The cross-sectional area of N2 molecules was 0.162nm. 2 The specific surface area of the samples was calculated using the BET method, and the pore distribution was calculated using the BJH method.
[0038] The morphology of the active sites of the catalyst before and after the reaction was observed using a spherical aberration corrected transmission electron microscope JEM-ARM200F STEM / TEM, with an operating voltage of 200 kV and a resolution of 0.08 nm. After the catalyst sample was ground, it was ultrasonically dispersed in ethanol, and the solution was dropped on a copper mesh to prepare a sample.
[0039] Embodiment 1:
[0040] Weigh 5 grams of 20-40 mesh, specific surface area 854m 2 / g activated carbon with a pore volume of 0.8cc / g was heated to 800℃ for 5 hours in nitrogen with a water vapor volume content of 20%. After impregnation with an equal volume of Co(NO3)2·5H2O solution according to the cobalt loading of 15% in the catalyst, it was dried and transferred to a tube furnace for calcination at 350℃ under nitrogen for 5 hours, and marked as 15Co / C.
[0041] According to the metal Mn loading of 0.5wt% in the catalyst, weigh manganese acetate and dissolve it in 10 ml of deionized water, stir to dissolve it, then add 15Co / C solid, add sodium carbonate to adjust pH=10, stir well, transfer to a Buchner funnel for suction filtration, wash to neutrality, and dry. According to the metal Na loading of 0.1wt% in the catalyst, prepare an equal volume of sodium carbonate solution for impregnation and dry. Transfer to a tubular furnace and roast again at 220°C under nitrogen for 5 hours, marked as 15Co-0.5Mn-0.1Na / C. The obtained solid is reduced with a mixture of 90% hydrogen and 10% nitrogen at 400°C for 4 hours, and then treated with CO gas at 450°C for 4 hours to obtain a 15Co@Co2C-0.5Mn-0.1Na / C nano core-shell catalyst.
[0042] The catalytic reaction was carried out in a fixed-bed high-pressure microreactor, with a volume ratio of H2 to CO in the synthesis gas of 2, a reaction pressure of 3.0 MPa, and a synthesis gas space velocity of 2000 mL g -1 ·h -1 , the reaction temperature was 210°C, and the reaction time was 100h. The reaction tail gas was analyzed online by gas chromatography, and its conversion rate was calculated by calculating the CO concentration and the reaction tail gas shrinkage rate. The product selectivity was calculated based on carbon, and the C1-C4 selectivity in the gas phase was calculated by the external standard method, C 5+ Hydrocarbons and alcohols were collected in cold traps and analyzed by off-line chromatography to obtain selectivity.
[0043] The active site structure of the catalyst after reduction and CO treatment was observed using a spherical aberration electron microscope, see Appendix Figure 1 and attached Figure 2. It can be seen that the active sites of the catalyst after reduction are mainly metal Co, which is distributed on the carbon support in the form of nanoparticles. Transition metal and alkali metal additives are distributed on the carbon support with a relatively high dispersion, and no clear crystalline phase is formed. After the metal Co nanoparticles are treated with CO, a part of them is converted into Co2C. The 15Co@Co2C-0.5Mn-0.1Na / C catalyst has an obvious nano core-shell structure, in which the lattice parameter of the core is 0.205nm, which is metal cobalt (fcc phase), and the lattice parameter of the shell is 0.247nm, which is cobalt carbide (Co2C). The average particle size of the core-shell structured cobalt nanoparticles formed after reconstruction is 12.5nm, the shell thickness is 4nm, and the core diameter is 4.5nm.
[0044] The specific reaction performance is listed in Appendix 1.
[0045] Example 2
[0046] Weigh 5 grams of 20-40 mesh, specific surface area 980m 2 / g activated carbon with a pore volume of 1.2cc / g was heated to 750℃ for 4 hours in nitrogen with a water vapor content of 30%. After being impregnated with an equal volume of Co(NO3)2·5H2O solution according to 20% of the cobalt loading in the catalyst, it was dried and transferred to a tube furnace for calcination at 400℃ for 5 hours, and marked as 20Co / C.
[0047] According to the metal Mn loading of 0.5wt% in the catalyst, manganese acetate is weighed and dissolved in 10 ml of deionized water, stirred to dissolve, and then 20Co / C solid is added, sodium carbonate is added to adjust the pH = 10, and after sufficient stirring, it is transferred to a Buchner funnel for suction filtration, washed to neutrality, and dried. According to the metal K loading of 0.3wt% in the catalyst, an equal volume of potassium nitrate solution is prepared for impregnation and then dried. Transfer to a tube furnace and roast again at 400°C for 5 hours, marked as 20Co-0.5Mn-0.3K / C. The obtained solid is reduced with 100% pure hydrogen at 470°C for 4 hours, and then treated with CO gas at 400°C for 10 hours to obtain a 20Co@Co2C-0.5Mn-0.3K / C nano core-shell catalyst. The active site structure of the catalyst after CO treatment is observed by spherical aberration electron microscopy. The active site of the catalyst is an obvious core-shell structure with an average particle size of 15nm, a shell thickness of 4.5nm, and a core diameter of 6nm. The transition metal and alkali metal additives are distributed on the carbon support with a relatively high dispersion degree without forming a clear crystalline phase.
[0048] The catalytic reaction was carried out in a fixed-bed high-pressure microreactor, with a volume ratio of H2 to CO in the synthesis gas of 3, a reaction pressure of 6.0 MPa, and a synthesis gas space velocity of 2000 mL g -1 ·h -1, the reaction temperature was 190°C, and the reaction time was 100h. The reaction tail gas was analyzed online by gas chromatography, and its conversion rate was calculated by calculating the CO concentration and the reaction tail gas shrinkage rate. The product selectivity was calculated based on carbon, and the C1-C4 selectivity in the gas phase was calculated by the external standard method, C 5+ Hydrocarbons and alcohols were collected in cold traps and analyzed by off-line chromatography to obtain selectivity.
[0049] The catalyst active site structure analysis method and product analysis are the same as in Example 1, and the reaction performance is shown in Appendix 1.
[0050] Example 3
[0051] Weigh 5 grams of 20-40 mesh, specific surface area 854m 2 / g activated carbon with a pore volume of 0.8cc / g was heated to 900℃ for 1 hour in nitrogen with a water vapor volume content of 10%. After impregnation with an equal volume of Co(NO3)2·5H2O solution according to the cobalt loading of 15% in the catalyst, it was dried and transferred to a tube furnace for calcination at 350℃ under nitrogen for 5 hours, marked as 15Co / C.
[0052] According to the metal Mn loading of 0.5wt% in the catalyst, weigh manganese nitrate and dissolve it in 10 ml of deionized water, stir to dissolve it, then add 15Co / C solid, add sodium carbonate to adjust the pH to 10, stir well, transfer to a Buchner funnel for suction filtration, wash to neutrality, and dry. According to the metal Mg loading of 1wt% in the catalyst, prepare an equal volume of magnesium nitrate solution for impregnation and dry. Transfer to a tube furnace and roast again at 300℃ for 5 hours, marked as 15Co-0.5Mn-1Mg / C. The obtained solid is reduced with a mixture of 70% hydrogen and 30% nitrogen at 300℃ for 4 hours, and then treated with CO gas at 470℃ for 4 hours to obtain a 15Co@Co2C-0.5Mn-1Mg / C nano core-shell catalyst. The active site structure of the catalyst after CO treatment was observed by spherical aberration electron microscopy. The active site structure of the catalyst after CO treatment was observed by spherical aberration electron microscopy. The active site of the catalyst is an obvious core-shell structure, with an average particle size of 13nm, a shell thickness of 4nm, and a core diameter of 5nm. The transition metal and alkali metal additives are distributed on the carbon carrier with a relatively high dispersion, and no clear crystalline phase is formed.
[0053] The catalytic reaction was carried out in a fixed-bed high-pressure microreactor, with a volume ratio of H2 to CO in the synthesis gas of 1, a reaction pressure of 2.5 MPa, and a synthesis gas space velocity of 2000 mL g -1 ·h -1, the reaction temperature was 270°C, and the reaction time was 100h. The reaction tail gas was analyzed online by gas chromatography, and its conversion rate was calculated by calculating the CO concentration and the reaction tail gas shrinkage rate. The product selectivity was calculated based on carbon, and the C1-C4 selectivity in the gas phase was calculated by the external standard method, C 5+ Hydrocarbons and alcohols were collected in cold traps and analyzed by off-line chromatography to obtain selectivity.
[0054] The catalyst active site structure analysis method and product analysis are the same as in Example 1, and the reaction performance is shown in Appendix 1.
[0055] Example 4
[0056] Weigh 5 grams of 20-40 mesh, specific surface area 854m 2 / g activated carbon with a pore volume of 0.8cc / g was heated to 600℃ for 2 hours in nitrogen with a water vapor volume content of 50%. After impregnation with an equal volume of Co(NO3)2·5H2O solution according to the cobalt loading of 15% in the catalyst, it was dried and transferred to a tube furnace for calcination at 350℃ under nitrogen for 5 hours, and marked as 15Co / C.
[0057] According to the metal Mn loading of 1wt% in the catalyst, manganese nitrate is weighed and dissolved in 10 ml of deionized water, stirred to dissolve, and then 15Co / C solid is added, sodium carbonate is added to adjust the pH = 10, and after sufficient stirring, it is transferred to a Buchner funnel for suction filtration, washed to neutrality, and dried. According to the metal Ca loading of 1wt% in the catalyst, an equal volume of calcium nitrate solution is prepared for impregnation and drying. Transfer to a tube furnace and roast again at 350°C for 5 hours, marked as 15Co-1Mn-1Ca / C. The obtained solid is reduced with a mixture of 90% hydrogen and nitrogen at 430°C for 4 hours, and then treated with CO gas at 490°C for 3 hours to obtain a 15Co@Co2C-1Mn-1Ca / C nano core-shell catalyst. The active site structure of the catalyst after CO treatment was observed by spherical aberration electron microscopy. The active site of the catalyst is an obvious core-shell structure with an average particle size of 14nm, a shell thickness of 5nm, and a core diameter of 4nm. The transition metal and alkali metal additives are distributed on the carbon support with a relatively high dispersion degree without forming a clear crystalline phase.
[0058] The catalytic reaction was carried out in a fixed-bed high-pressure microreactor, with a volume ratio of H2 to CO in the synthesis gas of 2, a reaction pressure of 3.0 MPa, and a synthesis gas space velocity of 2000 mL g -1 ·h -1 , the reaction temperature was 210°C, and the reaction time was 100h. The reaction tail gas was analyzed online by gas chromatography, and its conversion rate was calculated by calculating the CO concentration and the reaction tail gas shrinkage rate. The product selectivity was calculated based on carbon, and the C1-C4 selectivity in the gas phase was calculated by the external standard method, C 5+Hydrocarbons and alcohols were collected in cold traps and analyzed by off-line chromatography to obtain selectivity.
[0059] The catalyst active site structure analysis method and product analysis are the same as in Example 1, and the reaction performance is shown in Appendix 1.
[0060] Example 5
[0061] Weigh 5 grams of 20-40 mesh, specific surface area 918m 2 / g activated carbon with a pore volume of 1.0cc / g was heated to 900℃ for 4 hours in nitrogen with a water vapor content of 50%. After impregnation with an equal volume of Co(NO3)2·5H2O solution according to 20% of the cobalt loading in the catalyst, it was dried and transferred to a tube furnace for calcination at 300℃ for 5 hours, marked as 20Co / C.
[0062] According to the metal Mn loading of 2wt% in the catalyst, manganese nitrate is weighed and dissolved in 10 ml of deionized water, stirred to dissolve, and then 15Co / C solid is added, sodium carbonate is added to adjust the pH = 10, and after sufficient stirring, it is transferred to a Buchner funnel for suction filtration, washed to neutrality, and dried. According to the metal Mg loading of 1wt% in the catalyst, an equal volume of magnesium nitrate solution is prepared for impregnation and drying. Transfer to a tubular furnace and roast again at 330°C for 5 hours, marked as 20Co-2Mn-1Mg / C. The obtained solid is reduced with a mixture of 90% hydrogen and nitrogen at 500°C for 4 hours, and then treated with CO gas at 400°C for 7 hours to obtain a 20Co@Co2C-2Mn-1Mg / C nano core-shell catalyst. The active site structure of the catalyst after CO treatment is observed by spherical aberration electron microscopy. The active site of the catalyst is an obvious core-shell structure with an average particle size of 15nm, a shell thickness of 4.5nm, and a core diameter of 6nm. The transition metal and alkali metal additives are distributed on the carbon support with a relatively high dispersion degree without forming a clear crystalline phase.
[0063] The catalytic reaction was carried out in a fixed bed high pressure microreactor. The catalyst active site structure analysis method, reaction conditions and product analysis were the same as in Example 1. The reaction performance is shown in Appendix 1.
[0064] Example 6
[0065] 15Co / C was prepared as described in Example 1.
[0066] According to the loading amount of metal La in the catalyst of 2wt%, weigh lanthanum nitrate and dissolve it in 10 ml of deionized water, stir to dissolve it, then add 15Co / C solid, add sodium carbonate to adjust pH=10, stir well, transfer to Buchner funnel for suction filtration, wash to neutrality, and dry. According to the loading amount of metal Na in the catalyst of 0.5wt%, prepare an equal volume of sodium nitrate solution for impregnation, and then dry. Transfer to a tube furnace and roast again at 350℃ for 5 hours, marked as 15Co-2La-0.5Na / C. The obtained solid is reduced with a mixture of 90% hydrogen and nitrogen at 430℃ for 4 hours, and then treated with CO gas at 450℃ for 6 hours to obtain a 15Co@Co2C-2La-0.5Na / C nano core-shell catalyst. The active site structure of the catalyst after CO treatment was observed by spherical aberration electron microscopy. The active site of the catalyst is an obvious core-shell structure with an average particle size of 14nm, a shell thickness of 5nm, and a core diameter of 4nm. The transition metal and alkali metal additives are distributed on the carbon support with a relatively high dispersion degree without forming a clear crystalline phase.
[0067] The catalytic reaction was carried out in a fixed bed high pressure microreactor. The catalyst active site structure analysis method, reaction conditions and product analysis were the same as in Example 1. The reaction performance is shown in Appendix 1.
[0068] Example 7
[0069] 15Co / C was prepared as described in Example 1.
[0070] According to the loading amount of metal La in the catalyst of 1wt%, weigh lanthanum nitrate and dissolve it in 10 ml of deionized water, stir to dissolve it, then add 15Co / C solid, add sodium carbonate to adjust pH=10, stir well, transfer to Buchner funnel for suction filtration, wash to neutrality, and dry. According to the loading amount of metal K in the catalyst of 1wt%, prepare an equal volume of potassium nitrate solution for impregnation, and then dry. Transfer to a tube furnace and roast again at 350℃ for 5 hours, marked as 15Co-1La-1K / C. The obtained solid is reduced with a mixture of 90% hydrogen and nitrogen at 400℃ for 4 hours, and then treated with CO gas at 460℃ for 4 hours to obtain a 15Co@Co2C-1La-1K / C nano core-shell catalyst. The active site structure of the catalyst after CO treatment was observed by spherical aberration electron microscopy. The active site of the catalyst is an obvious core-shell structure with an average particle size of 12nm, a shell thickness of 3nm, and a core diameter of 6nm. The transition metal and alkali metal additives are distributed on the carbon support with a relatively high dispersion degree without forming a clear crystalline phase.
[0071] The catalytic reaction was carried out in a fixed bed high pressure microreactor. The catalyst active site structure analysis method, reaction conditions and product analysis were the same as in Example 1. The reaction performance is shown in Appendix 1.
[0072] Example 8
[0073] 15Co / C was prepared as described in Example 1.
[0074] According to the metal Ce loading of 2wt% in the catalyst, weigh cerium nitrate and dissolve it in 10 ml of deionized water, stir to dissolve it, then add 15Co / C solid, add sodium carbonate to adjust PH=10, stir well, transfer to Buchner funnel for suction filtration, wash to neutrality, and dry. According to the metal Li loading of 0.5wt% in the catalyst, prepare an equal volume of lithium nitrate solution for impregnation and dry. Transfer to a tube furnace and roast again at 350℃ for 5 hours, marked as 15Co-2Ce-0.5Li / C. The obtained solid is reduced with a mixture of 90% hydrogen and nitrogen at 430℃ for 4 hours, and then treated with CO gas at 480℃ for 4 hours to obtain 15Co@Co2C-2Ce-0.5Li / C nano core-shell catalyst. The active site structure of the catalyst after CO treatment was observed by spherical aberration electron microscopy. The active site of the catalyst is an obvious core-shell structure with an average particle size of 10nm, a shell thickness of 3nm, and a core diameter of 4nm. The transition metal and alkali metal additives are distributed on the carbon support with a relatively high dispersion degree without forming a clear crystalline phase.
[0075] The catalytic reaction was carried out in a fixed bed high pressure microreactor. The catalyst active site structure analysis method, reaction conditions and product analysis were the same as in Example 1. The reaction performance is shown in Appendix 1.
[0076] Example 9
[0077] As described in Example 2, 20Co / C was prepared.
[0078] According to the metal Mn loading of 2wt% in the catalyst, manganese acetate was weighed and dissolved in 10 ml of deionized water, stirred to dissolve, and then 15Co / C solid was added, sodium carbonate was added to adjust the pH = 10, and after sufficient stirring, it was transferred to a Buchner funnel for suction filtration, washed to neutrality, and dried. According to the metal Li loading of 0.5wt% in the catalyst, an equal volume of lithium nitrate solution was prepared for impregnation and then dried. Transferred to a tube furnace and roasted again at 350°C for 5 hours, marked as 20Co-2Mn-0.5Li / C. The obtained solid was reduced with a mixture of 90% hydrogen and nitrogen at 470°C for 4 hours, and then treated with CO gas at 490°C for 3 hours to obtain a 20Co@Co2C-2Mn-0.5Li / C nano core-shell catalyst. The active site structure of the catalyst after CO treatment was observed by spherical aberration electron microscopy. The active site of the catalyst is an obvious core-shell structure with an average particle size of 15nm, a shell thickness of 6nm, and a core diameter of 3nm. The transition metal and alkali metal additives are distributed on the carbon support with a relatively high dispersion degree without forming a clear crystalline phase.
[0079] The catalytic reaction was carried out in a fixed bed high pressure microreactor. The catalyst active site structure analysis method, reaction conditions and product analysis were the same as in Example 1. The reaction performance is shown in Appendix 1.
[0080] Example 10
[0081] As described in Example 2, 20Co / C was prepared.
[0082] According to the loading amount of lanthanum metal in the catalyst of 2wt%, weigh lanthanum nitrate and dissolve it in 10 ml of deionized water, stir to dissolve it, then add 20Co / C solid, add sodium carbonate to adjust pH=10, stir well, transfer to Buchner funnel for suction filtration, wash to neutrality, and dry. According to the loading amount of metal Ba in the catalyst of 1wt%, prepare an equal volume of barium nitrate solution for impregnation, and then dry. Transfer to a tube furnace and roast again at 350℃ for 5 hours, marked as 20Co-2La-1Ba / C. The obtained solid is reduced with a mixture of 90% hydrogen and nitrogen at 470℃ for 4 hours, and then treated with CO gas at 470℃ for 2 hours to obtain 20Co@Co2C-2La-1Ba / C nano core-shell catalyst. The active site structure of the catalyst after CO treatment was observed by spherical aberration electron microscope. The active site of the catalyst is an obvious core-shell structure with an average particle size of 15nm, a shell thickness of 5nm, and a core diameter of 5nm. The transition metal and alkali metal additives are distributed on the carbon support with a relatively high dispersion degree without forming a clear crystalline phase.
[0083] The catalytic reaction was carried out in a fixed bed high pressure microreactor. The catalyst active site structure analysis method, reaction conditions and product analysis were the same as in Example 1. The reaction performance is shown in Appendix 1.
[0084] Embodiment 11
[0085] As described in Example 2, 20Co / C was prepared.
[0086] According to the cerium metal loading of 3wt% in the catalyst, weigh cerium nitrate and dissolve it in 10 ml of deionized water, stir to dissolve it, then add 20Co / C solid, add sodium carbonate to adjust pH=10, stir well, transfer to a Buchner funnel for suction filtration, wash to neutrality, and dry. According to the potassium metal loading of 1wt% in the catalyst, prepare an equal volume of potassium nitrate solution for impregnation and dry. Transfer to a tube furnace and roast again at 350°C for 5 hours, marked as 20Co-3Ce-1K / C. The obtained solid is reduced with a mixture of 90% hydrogen and nitrogen at 470°C for 4 hours, and then treated with CO gas at 450°C for 4 hours to obtain a 20Co@Co2C-3Ce-1K / C nano core-shell catalyst. The active site structure of the catalyst after CO treatment was observed by spherical aberration electron microscopy. The active site of the catalyst is an obvious core-shell structure with an average particle size of 15nm, a shell thickness of 4.5nm, and a core diameter of 6nm. The transition metal and alkali metal additives are distributed on the carbon support with a relatively high dispersion degree without forming a clear crystalline phase.
[0087] The catalytic reaction was carried out in a fixed bed high pressure microreactor. The catalyst active site structure analysis method, reaction conditions and product analysis were the same as in Example 1. The reaction performance is shown in Appendix 1.
[0088] Example 12
[0089] Weigh 5 grams of 20-40 mesh, specific surface area 967m 2 / g activated carbon with a pore volume of 1.2cc / g was heated to 800℃ for 4 hours in nitrogen with a water vapor content of 30%. After being impregnated with an equal volume of Co(NO3)2·5H2O solution according to a cobalt loading of 25%, it was dried and transferred to a tube furnace for calcination at 220℃ for 5 hours, and marked as 25Co / C.
[0090] According to the cerium metal loading of 5wt% in the catalyst, weigh cerium nitrate and dissolve it in 10 ml of deionized water, stir to dissolve it, then add 25Co / C solid, add sodium carbonate to adjust pH=10, stir well, transfer to a Buchner funnel for suction filtration, wash to neutrality, and dry. According to the potassium metal loading of 2wt% in the catalyst, prepare an equal volume of potassium nitrate solution for impregnation and dry. Transfer to a tube furnace and roast again at 350°C for 5 hours, marked as 25Co-5Ce-2K / C. The obtained solid is reduced with a mixture of 90% hydrogen and nitrogen at 500°C for 4 hours, and then treated with CO gas at 500°C for 4 hours to obtain a 25Co@Co2C-5Ce-2K / C nano core-shell catalyst. The active site structure of the catalyst after CO treatment was observed by spherical aberration electron microscopy. The active site of the catalyst is an obvious core-shell structure with an average particle size of 15nm, a shell thickness of 6.5nm, and a core diameter of 2nm. The transition metal and alkali metal additives are distributed on the carbon support with a relatively high dispersion degree without forming a clear crystalline phase.
[0091] The catalytic reaction was carried out in a fixed bed high pressure microreactor. The catalyst active site structure analysis method, reaction conditions and product analysis were the same as in Example 1. The reaction performance is shown in Appendix 1.
[0092] Comparative Example 1
[0093] According to the method described in Example 1, a 15Co / C catalyst was prepared as Comparative Example 1, and then reduced in a mixture of 90% hydrogen and nitrogen at 400°C for 5 hours without CO treatment, and then directly evaluated in a fixed bed high pressure microreactor. The reaction conditions and product analysis were the same as in Example 1, and the reaction performance is shown in Appendix 1. The active site nanoparticle structure was characterized by ac-STEM, see Appendix Figure 3 It can be seen that the active sites of the catalyst are metal Co nanoparticles (fcc-Co, d = 0.207nm), rather than core-shell structures. The content of alcohol and olefin in the product is very low.
[0094] Comparative Example 2
[0095] According to the method described in Example 1, the transition element was replaced by the main group element Al, and the other conditions remained unchanged to prepare a 15Co-0.5Al-0.1Na / C catalyst, which was then reduced in a mixture of 90% hydrogen and nitrogen at 400°C for 5 hours. The obtained solid was treated with CO gas at 490°C for 4 hours and then evaluated in a fixed bed high pressure microreactor. The reaction conditions and product analysis were the same as in Example 1. The reaction performance is shown in Appendix 1. The catalyst active site structure was analyzed by ac-STEM, see Appendix Figure 4 It can be seen that the active sites of the catalyst are mainly cobalt carbide particles (Co2C, d = 0.245nm), and it is not a nano-core-shell structure, and the catalyst activity is very low. This result shows that the doping of a series of metal elements represented by the main group element Al cannot play the role of forming a core-shell structure.
[0096] Comparative Example 3
[0097] According to the method described in Example 1, the original activated carbon that has not been treated with nitrogen containing water vapor (i.e., the carrier has no nitrogen treatment process containing water vapor), and the other conditions remain unchanged to prepare 15Co@Co2C-0.5Mn-0.1Na / UC nano core-shell catalyst. Then it was evaluated in a fixed bed high-pressure microreactor, and the reaction conditions and product analysis were the same as in Example 1, and the reaction performance was shown in Attached Table 1. The comparative results show that the activated carbon that has not been treated with water vapor has a significantly lower activity than the sample treated with water vapor, and the selectivity is similar. The analysis shows that the active site of the catalyst is also a nano core-shell structure, but there are a large number of cobalt species (mainly cobalt carbide Co2C) agglomerates with an equivalent diameter of more than 100nm on the carrier, and the average particle size of cobalt is about 30nm, which is much larger than the 15nm treated with water vapor. Therefore, it is believed that the water vapor treatment mainly plays a role in improving the dispersion of the active sites of the catalyst and improving the activity.
[0098] Comparative Example 4
[0099] According to the method described in Example 1, 15Co / C was prepared, and then manganese acetate was weighed and dissolved in 10 ml of deionized water according to the metal Mn loading of 0.5wt%, and stirred to dissolve, and then 15Co / C solid was added, stirred thoroughly, and dried. Transferred to a tubular furnace and calcined at 350°C for 5 hours, marked as 15Co-0.5Mn / C. Then reduced at 400°C in a mixture of 90% hydrogen and nitrogen for 5 hours, the obtained solid was treated with CO gas at 490°C for 4 hours, and evaluated in a fixed bed high-pressure microreactor. The reaction conditions and product analysis were the same as in Example 1, and the reaction performance is shown in Appendix 1. The catalyst active site structure was analyzed by ac-STEM, see Appendix Figure 5 It can be seen that no obvious nano-core-shell structure is formed, and the main particles are metal Co nanoparticles. The selectivity of alcohols and olefins is also lower than that of the catalyst with obvious nano-core-shell structure.
[0100] Comparative Example 5
[0101] According to the method described in Example 1, 15Co-0.5Mn-0.1Na / C catalyst was prepared, and then directly in a high-pressure microreactor without CO treatment, CO:H2=2:1 synthesis gas conditions, 220°C, 3MPa evaluation, reaction conditions and product analysis are the same as in Example 1, the microstructure of the catalyst active site is shown in the attached Figure 6 The reaction performance is shown in Table 1. The analysis results show that the catalyst without CO treatment does not form an obvious nano-core-shell structure, and the selectivity of alcohols and olefins in the product is low. This shows that CO treatment is necessary for the generation of Co2C and the improvement of the selectivity of alcohols and olefins.
[0102] Appendix 1 Performance comparison of nano core-shell cobalt-based catalysts and conventional Co / C catalysts
[0103]
[0104] In summary, it can be seen that the cobalt-based catalyst with a nano core-shell structure, with metal cobalt as the core and cobalt carbide as the shell, has a much higher overall selectivity and yield of olefins and alcohols than conventional cobalt-based catalysts (with metal cobalt as the active center), among which high carbon alcohols (C 6+ Alcohols) and higher olefins (C 5+ The content of olefins) in total alcohols and olefins exceeds 80%. It is proved that the joint action of several transition metals and alkali metals, as well as the pre-treatment step of CO atmosphere, is the key factor for the catalyst to form a core-shell structure active center, and to improve the total selectivity and yield of catalyst alcohols and olefins. Among them, the loading amount of metal Co has the most obvious effect on the catalyst activity. Increasing the Co loading amount helps to improve the activity, but the loading amount has little effect after exceeding a certain value. The preferred combination of several transition metals and alkali metals can obtain higher alcohol and olefin selectivity. The catalyst active sites obtained under the corresponding reduction and CO treatment conditions have similar core-shell structures and similar performances. The method of treating the carbon carrier with water vapor can significantly improve the activity of the catalyst. Although the carrier without water vapor treatment also has good alcohol / olefin total selectivity, the catalyst activity is low, resulting in a very low total yield.
Claims
1. A nano core-shell cobalt-based catalyst, characterized in that: The catalyst comprises a porous carbon carrier, an additive and cobalt nanoparticles with a core-shell structure supported on the porous carbon carrier, wherein the metal cobalt is coated by a cobalt carbide shell to form a core-shell structure; The cobalt content in the catalyst is between 10 wt% and 30 wt%; the promoter includes a transition metal promoter and an alkali metal and / or alkaline earth metal promoter; the transition metal promoter is one or more of Mn, La and Ce, and the weight content thereof in the catalyst is between 0.1 wt% and 5 wt% by metal mass; the alkali metal or alkaline earth metal promoter is one or more of Li, Na, K, Ca, Mg and Ba, and the weight content thereof in the catalyst is between 0.01 wt% and 2 wt% by metal mass; The method for preparing the nano core-shell cobalt-based catalyst is characterized by comprising the following steps: 1) The activated carbon is treated at high temperature with a mixture of water vapor and nitrogen to obtain a carbon carrier; the volume concentration of the water vapor in the nitrogen is 10-50%, the treatment temperature is 600-900°C, and the treatment time is 1-5 hours; 2) dissolving a soluble cobalt salt in water to prepare an impregnation solution, and using an equal volume impregnation method to load the cobalt precursor on a carbon support to prepare a catalyst precursor; 3) The catalyst precursor is calcined in an inert gas to convert the cobalt precursor into cobalt oxide nanoparticles dispersed on the surface of the carrier to obtain a solid sample; 4) Add the precursor salt of the transition metal additive to deionized water to prepare a solution, then add the solid sample obtained in (3), stir, add one or both of sodium carbonate or potassium carbonate, and adjust the pH. The value is 9-12, stirring, filtering, washing to neutrality and drying; 5) using an equal volume impregnation method, impregnating the solid obtained in (4) with an aqueous solution of an alkali metal and / or alkaline earth metal salt, drying and then roasting again in an inert gas; 6) reducing the catalyst precursor obtained in step (5) to convert the cobalt oxide into metallic cobalt nanoparticles to obtain a reduced catalyst; 7) treating the reduced catalyst obtained in (6) under a carbon monoxide atmosphere, during which the metal cobalt nanoparticles are reconstructed to form the nano core-shell cobalt-based catalyst; the treatment temperature is between 400 and 500 °C; and the treatment time is between 2 and 10 hours.
2. The nano core-shell cobalt-based catalyst according to claim 1, characterized in that The cobalt content in the catalyst is 15 wt%-25 wt%; the weight content of the transition metal promoter in the catalyst is 0.3 wt%-3 wt% based on the weight of the metal; the weight content of the alkali metal or alkaline earth metal promoter in the catalyst is 0.1 wt%-1 wt% based on the weight of the metal; The method for preparing the nano core-shell cobalt-based catalyst is characterized by comprising the following steps: Step 1) the volume concentration of water vapor in nitrogen is 20-30%, the treatment temperature is 700-800°C, and the treatment time is 2-4 hours; Step 7) The treatment temperature is between 450 and 490°C; the treatment time is between 3 and 7 hours.
3. The nano core-shell cobalt-based catalyst according to claim 2, characterized in that The cobalt content in the catalyst is 15 wt%-20 wt%; the weight content of the transition metal additive in the catalyst is 0.5 wt%-2 wt% based on the metal mass.
4. The nano core-shell cobalt-based catalyst according to claim 1, characterized in that The particle size of the core-shell structured cobalt nanoparticles is 10-15 nm, the particle size of the metal cobalt grains as the core is 2-6 nm, and the metal cobalt is coated with a cobalt carbide shell to form a core-shell structure. The cobalt carbide is a compound Co2C formed by cobalt and carbon.
5. The preparation method according to claim 1, characterized in that: The activated carbon described in step (1) has a specific surface area of 800-1000 m 2 / g, and the pore volume is between 0.8~1.2 cc / g.
6. The preparation method according to claim 1, characterized in that: The precursor salts of the transition metal additive described in step (4) include one or more chlorides, sulfates and nitrates of one or more of Mn, La and Ce; the alkali metal and alkaline earth metal salts described in step (5) include one or more chlorides, sulfates and nitrates of one or more of Li, Na, K, Ca, Mg and Ba.
7. The preparation method according to claim 1, characterized in that: The calcination temperature in steps (3) and (5) is between 220 and 400° C., the calcination atmosphere is one or both of nitrogen and argon, and the calcination time is between 2 and 6 hours.
8. The preparation method according to claim 7, characterized in that: The calcination temperature in steps (3) and (5) is 300-350° C. and the calcination time is 3-4 hours.
9. The preparation method according to claim 1, characterized in that: In step (6), the reducing atmosphere is hydrogen, or a mixture of hydrogen and nitrogen, and the volume content of hydrogen in the reducing atmosphere is between 50% and 100%; the reducing temperature is between 300 and 500° C., and the reducing time is between 2 and 6 hours.
10. The preparation method according to claim 9, characterized in that: In step (6), the reducing atmosphere is hydrogen, or a mixture of hydrogen and nitrogen, the volume content of hydrogen in the reducing atmosphere is between 70% and 100%; the reducing temperature is between 400 and 470° C.; and the reducing time is between 3 and 4 hours.
11. Use of the nano core-shell cobalt-based catalyst according to any one of claims 1 to 4 in catalyzing the direct production of alcohols and olefins from synthesis gas.
12. The use according to claim 11, characterized in that The reaction is carried out in a fixed bed reactor, the molar ratio of CO to H2 in the synthesis gas is 1:1~1:3, the reaction temperature is 190~270 ℃, and the reaction pressure is 2.5~6 MPa.
Citation Information
Patent Citations
Preparation method and application of core-shell structure cobalt-base catalyst of middle distillate for synthesis gas preparation
CN101804351A
A core-shell catalyst for the direct synthesis of low-carbon olefins from syngas, its preparation method and application.
CN104888838B
Synthesis gas catalytic conversion catalyst and preparation method of synthesis gas catalytic conversion catalyst
CN108126701A
Core-shell type cobalt-based Fischer-Tropsch synthesis catalyst and preparation method therefor
CN108654638A